The impact of the implementation of economic, social, and good corporate governance (ESG) on the performance of esg-listed companies on the Indonesia stock exchange - Waluyo, Herlina; Suk, Kim Sung (Enrichment : Journal of Management, 2023)
The implementation of Economic, Social, and Good Corporate Governance (ESG) is expected to enhance company performance by reducing the risks faced by investors. This study will examine how the implementation of ESG influences company performance, measured using Return on Assets (ROA), with the hypothesis that ESG has a positive impact on company performance. The data used are from secondary sources, with a sample of 84 companies and a total of 298 observations through unbalanced panel data with a fixed-effect model regression. The research results indicate a negative impact of ESG on company performance due to a lack of awareness and education about sustainability practices. To increase awareness of ESG implementation, adequate regulations and law enforcement are needed to enhance the appeal of green projects.